1989
DOI: 10.4039/ent121623-7
|View full text |Cite
|
Sign up to set email alerts
|

A NEW PEST IN CANADA: RUSSIAN WHEAT APHID, DIURAPHIS NOXIA (MORDVILKO) (HOMOPTERA: APHIDIDAE)

Abstract: Russian wheat aphid, Diuraphis noxia, was first detected in Canada in late July 1988 when a few were found on late-maturing spring cereals in southern Alberta near the International Boundary between Coutts and Aden. By the end of September, after dispersal or further immigration influx, it was widespread in Alberta south of Highway #3 and in southwestern Saskatchewan as far east as Swift Current. By mid-October more than 30% of the plants in many fields of winter wheat and fall rye in southern Alberta and up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 5 publications
0
9
0
3
Order By: Relevance
“…Very infested plants have less dry weight, leaf area, and chlorophyll (Gilchist et al 1984, Miller et al 1994, Riedell and Blackmer 1999 Although the Russian wheat aphid is widely distributed, its economic impact on small grains has been assessed only in South Africa, the US, and Canada Bynum 1992, Lage et al 2004). Since its discovery in Texas in 1986, it has rapidly spread across the US and infested wheat and barley fields in 17 western states and three Canadian provinces (Jones et al 1989, Kindler et al 1992, Legg et al 1994. Economic injury levels caused by Russian wheat aphid feeding on small grains vary within a region (Gray et al 1990, Archer and Bynum 1992, Archer et al 1998, Randolph et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Very infested plants have less dry weight, leaf area, and chlorophyll (Gilchist et al 1984, Miller et al 1994, Riedell and Blackmer 1999 Although the Russian wheat aphid is widely distributed, its economic impact on small grains has been assessed only in South Africa, the US, and Canada Bynum 1992, Lage et al 2004). Since its discovery in Texas in 1986, it has rapidly spread across the US and infested wheat and barley fields in 17 western states and three Canadian provinces (Jones et al 1989, Kindler et al 1992, Legg et al 1994. Economic injury levels caused by Russian wheat aphid feeding on small grains vary within a region (Gray et al 1990, Archer and Bynum 1992, Archer et al 1998, Randolph et al 2003.…”
Section: Introductionmentioning
confidence: 99%
“…The Russian wheat aphid, Diuraphis noxia (Kurdjumov), is a devastating global pest of bread wheat, Triticum aestivum L., durum wheat, T. turgidum L. and barley, Hordeum vulgare L. [1][2][3] The cumulative losses to all US small grain production due to D. noxia control, grain losses and lost community economic activity from 1986 to 1993 were valued at~$1 billion. 4 For US barley, D. noxia infestation of 0.7 million ha in 1992 caused losses of~$18.5 million.…”
Section: Introductionmentioning
confidence: 99%
“…It spread rapidly throughout the western cereal growing regions of the United States and Canada (Jones et al 1989), and by 1990, it was found in 16 western states and three Canadian provinces. Host plants of the Russian wheat aphid include wheat, Triticum aestivum L., barley, Hordeum vulgare L., and several species of noncultivated Graminae (Kindler and Springer 1989).…”
mentioning
confidence: 99%